Acute care pathways for patients calling the out-of-hours services - Morten Breinholt Søvsø; Linda Huibers; Bodil Hammer Bech; Helle Collatz Christensen; Morten Bondo Christensen; Erika Frischknecht Christensen (BMC, 2020)
Abstract Background In Western countries, patients with acute illness or injury out-of-hours (OOH) can call either emergency medical services (EMS) for emergencies or primary care services (OOH-PC) in less urgent situations. Callers initially choose which service to contact; whether this choice reflect the intended differences in urgency and severity is unknown. Hospital diagnoses and admission rates following an OOH service contact could elucidate this. We aimed to investigate and compare the prevalence of patient contacts, subsequent hospital contacts, and the age-related pattern of hospital diagnoses following an out-of-hours contact to EMS or OOH-PC services in Denmark. Methods Population-based observational cohort study including patients from two Danish regions with contact to EMS or OOH-PC in 2016. Hospital contacts were defined as short (< 24 h) or admissions (≥24 h) on the date of OOH service contact. Both regions have EMS, whereas the North Denmark Region has a general practitioner cooperative (GPC) as OOH-PC service and the Capital Region of Copenhagen the Medical Helpline 1813 (MH-1813), together representing all Danish OOH service types. Calling an OOH service is mandatory prior to a hospital contact outside office hours. Results OOH-PC handled 91% (1,107,297) of all contacts (1,219,963). Subsequent hospital contacts were most frequent for EMS contacts (46-54%) followed by MH-1813 (41%) and GPC contacts (9%). EMS had more admissions (52-56%) than OOH-PC. For both EMS and OOH-PC, short hospital contacts often concerned injuries (32-63%) and non-specific diagnoses (20-45%). The proportion of circulatory disease was almost twice as large following EMS (13-17%) compared to OOH-PC (7-9%) in admitted patients, whereas respiratory diseases (11-14%), injuries (15-22%) and non-specific symptoms (22-29%) were more equally distributed. Generally, admitted patients were older. Conclusions EMS contacts were fewer, but with a higher percentage of hospital contacts, admissions and prevalence of circulatory diseases compared to OOH-PC, perhaps indicating that patients more often contact EMS in case of severe disease. However, hospital diagnoses only elucidate severity of diseases to some extent, and other measures of severity could be considered in future studies. Moreover, the socio-demographic pattern of patients calling OOH needs exploration as this may play an important role in choice of entrance.